Prevailing of anaerobic soil disinfestation (ASD) with diluted ethanol for Eustoma grandiflorum production in Geisei Village, Kochi - KOBARA, Yuso (Journal of the NARO Research and Development, 2025)
The production of ornamental plants continues to be a prospering and expanding industry across Japan. The most destructive pathogenic microorganisms for ornamental production are the soil-borne Fusarium wilt diseases pathogen, Fusarium oxysporum and bacterial wilt disease pathogen, Ralstonia solanacearum and Burkholderia caryophylli against Eustoma grandiflorum (lisianthus) plants in Japan. Once these diseases have broken out, plants are rarely suitable for commercialization. When the diseases have become established in a production system, many approaches for achieving suppression have been explored, but most have not met the high standard for zero diseases threshold demanded by the industry. Anaerobic soil disinfestation with diluted ethanol (Et-ASD) is gradually spreading as one of the promising soil disinfection techniques. In most cases of Et-ASD in Eustoma, satisfactory results at practical levels have been obtained against soil-borne disease. However, to encourage further prevailing Et-ASD, it is necessary to address grower-driven research questions, to define the minimum input rates needed to reduce costs, and to demonstrate a stable soil disease suppression effect and to steadily promote its use based on the advantages and economic evaluation of Et-ASD. The purposes of our study were to demonstrate areawide Et-ASD in a lisianthus monoculture in Gesisei Village, Kochi Prefecture to get observer perceptions and economic analysis of the treatments and results and to gain useful feedback for the future research approach.